Expansive Learning Within a Teachers Community of Ongoing Learners (TCOOL) - Rust, Frances O.; Dunn, Meghan; Silverstein, Sabrina (Frontiers in Education, 2020)
This paper presents a first iteration of the TCOOL project as a design experiment in the education of teachers for high poverty, urban schools. The TCOOL Project embodies a new vision for the professional education of teachers that engages schools and universities in deep partnership designed to support the preparation and on-going learning of teachers. Expansive learning theory as described by Engeström and his colleagues is used to probe the opportunities for learning about teaching that TCOOL provides to practitioners in schools and universities. We found that the expansive learning theory enabled us to see that, even in its pilot run, the learning processes manifested throughout by participants in the school and university included productive deviations from our original intentions. These have led to both practical and theoretical shifts in our change effort.